Minocycline affects human neutrophil respiratory burst and transendothelial migration - Parenti, Astrid; Indorato, Boris; Paccosi, Sara (Inflammation research, 2017)
Objective This study aimed at investigating the in vitro activity of minocycline and doxycycline on human polymorphonuclear (h-PMN) cell function. Methods h-PMNs were isolated from whole venous blood of healthy subjects; PMN oxidative burst was measured by monitoring ROS-induced oxidation of luminol and transendothelial migration was studied by measuring PMN migration through a monolayer of human umbilical vein endothelial cells. Differences between multiple groups were determined by ANOVA followed by Tukey’s multiple comparison test; Student’s t test for unpaired data for two groups. Results Minocycline (1–300 µM) concentration dependently and significantly inhibited oxidative burst of h-PMNs stimulated with 100 nM fMLP. Ten micromolar concentrations, which are superimposable to C max following a standard oral dose of minocycline, promoted a 29.8 ± 4 % inhibition of respiratory burst ( P < 0.001; n = 6). Doxycycline inhibited ROS production with a lesser extent and at higher concentrations. 10–100 µM minocycline impaired PMN transendothelial migration, with maximal effect at 100 µM (42.5 ± 7 %, inhibition, n = 5, P < 0.001). Conclusions These results added new insight into anti-inflammatory effects of minocycline exerted on innate immune h-PMN cell function.